Imagination and Literacy: A Teacher's Search for the Heart of Learning - Gordon Wells (Networks: An Online Journal for Teacher Research, 2005)
Ever since her first book, The Languages of Learning: How children talk, write, dance, draw, and sing their understanding of the world (1994), Karen Gallas has delighted and informed her readers about what primary schoolchildren can achieve when their teacher is genuinely interested in their contributions to classroom activities and, as a teacher researcher, collects and reflects on the data that they so willingly provide. This book continues that tradition, but with a significant addition. In Imagination and Literacy, Gallas continues to draw on her corpus of classroom observational data, but with a difference. Here, her focus is on the nature of imagination and its central role in learning, not only for children but for learners of all ages.